Manajemen Kinerja Di Sektor Publik High-Cost: Kesiapan Operasional Direktorat Kepolisian Udara Di Tengah Kebijakan Efisiensi Anggaran - Ikhsan, Muhammad; Subroto, Rexy Hamza; Savior, Robith Hasbi (UIR Press, 2026)
Fiscal efficiency policies driven by external economic contexts are often implemented uniformly across public organizations. However, this approach triggers a managerial dilemma for high-cost and high-risk agencies, such as the Directorate of Air Police (Ditpoludara) Baharkam Polri. This conceptual paper aims to dissect the implications of budget efficiency on the operational readiness of Ditpoludara through the lens of public performance management. Utilizing a theoretical analysis design (desk research), this study demonstrates that the dominant fixed-cost structure of aviation equipment forces efficiency measures to slash variable costs, specifically tactical training flight hours. This reduction degrades personnel's Knowledge, Skills, & Abilities (KSA), which are highly perishable. Consequently, it induces a False Positive risk, where personnel are administratively deemed flight-ready despite a decline in actual psychomotor proficiency, thereby jeopardizing aviation safety. This study recommends implementing managerial flexibility by optimizing flight simulator technology to retain KSA, alongside reforming the planning function through a Risk-Based Budgeting model.